A dimorphic magnetorheological elastomer incorporated with Fe nano-flakes modified carbonyl iron particles: preparation and characterization. (12th October 2015) - Yu, M; Zhu, M; Fu, J; Yang, P A; Qi, S
Abstract: This paper describes a simple and convenient approach for the synthesis of Fe nano-flakes coated spherical carbonyl iron particles (CIP-Nano-Fe). The morphology and composition of CIP-Nano-Fe were characterized using electron scanning microscope and x-ray diffraction analysis. The results indicated that the CI particles were coated with uniform and continuous Fe nanostructures. Partial substitution of CI particles with CIP-Nano-Fe constituted a novel dimorphic magnetorheological elastomer (D-MRE), and the influence of the content of CIP-Nano-Fe on the viscoelastic performance of the magnetorheological elastomers (MREs) were systematically studied. The magnetorheological properties and the damping properties of the D-MRE samples were analyzed to evaluate their dynamic properties. The experimental results indicated that the MR effect, the max loss factor and the magneto-induced loss factor in the sample 3 (CIP-Nano-Fe weight content 6 wt%) were approximately 1.32, 1.45 and 1.56 times that in the sample 1 (non-doped MRE). The approach to synthesize CIP-Nano-Fe reported here can be readily explored for fabricating particles modified by other metal nanostructures, and the resulting D-MREs are expected to be applied in various applications, especially in the field of vibration and noise control, involving vibration isolators, tunable engine mounts, noise insulation devices, and so forth.